Investigative Impact of Serum IL-6 and TNF-α Levels in Pediatric Diarrhea Patients with listeria monocytogenes Infection - AL-Hammami, Hind (Medical Science Journal for Advance Research, 2024)
Background: In children, diarrhea is a significant cause of morbidity and severe mortality. Infection with pathogens as Listeria monocytogenes is one of the etiological reasons that can result in diarrhea. Important inflammatory markers in bacterial diarrhea in children include the IL-6, TNF-α, blood markers CRP, WBC, and Absolute Neutrophil Count, It can be important in the initial diagnosis of an infection. Objectives: This investigation intended to measure some immunological markers (such as IL-6 and TNF-α and other blood markets such as CRP, WBC, and Absolute Neutrophil Count ) in children with diarrhea, especially with the emergence of Listeria monocytogenes bacteria isolates to the considerate corresponding immune system to get rid pathogen. Methods: From November 2022 until the end of July 2023, 480 suspected patients with acute diarrhea infection who attended the AL-Zahraa Teaching Hospital were registered, encompassing both sexes, and children aged 1 to 5 years. Patients’ stool samples were cultivated on certain conditions, and bacterial isolates were subsequently identified using morphological, biochemical, and API techniques. After receiving consent from patients and ethical advice from hospitals, the blood and serum levels of immunological markers were evaluated in various groups. Results: Present study revealed that L.monocytogenes .recovered at 8.3% of cases(no=40 total isolate), Mean age of the disease was 3.3±2.32 years, the percentage of infection in males(72.5% ) more than females( 32.5%), There were notable increasing in P-value of CRP, serum IL-6, serum TNF-α, WBCs and ANC in children with diarrhea associated with L.monocytogenes compared to the control group (p˂0.05) with highly sensitivity and specificity. Conclusion: Data revealed the coordinated role between study immune markers responding to acute diarrhea in children and consider suitable markers.